ANALYTICAL METHOD DEVELOPMENT FOR THE ESTIMATION OF DARUNAVIR BY DIAZOTIZATION AND COUPLING BY VISIBLE SPECTROPHOTOMETRY - R, Vijayalakshmi; D, Anjani; M, Sriramamurthy; M D, Dhanaraju (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: This proposed work describes simple and extraction free visible methods for the estimation of darunavir ethanolate (DNV) in bulk and tablet formulations. The methodology involves diazotization of DNV with nitrous acid followed by coupling with chromotropic acid (CA) (Method A)/ Bratton Marshall Reagent (Method B)/α-naphthol (Method C) to form colored products. Methods: All the methods were developed using a PerkinElmer (LAMBDA 25) UV–Visible spectrophotometer interfaced with UV Win lab software and 1 cm quartz cells. Results: Spectrophotometrically, DNV is estimated at 520 nm, 544 nm, and 464 nm for the reddish-pink color produced by CA, dark violet color with NED, and dark-greenish yellow with α-naphthol, respectively. The linear relationship was observed between absorbance and the corresponding concentration of drug in the range of 100–350 μg/mL, 10–100 μg/mL, and 10–60 μg/mL for Methods A, B, and C, respectively. Conclusion: The colorimetric methods were extensively validated as per the ICH guidelines. The developed methods were proven to be more accurate and precise by the statistical analysis.